KERJA PASAK BUMI (Eurycoma Longifolia. JACK) TERHADAP TINGKAH LAKU DAN LIBIDO TIKUS PUTIH JANTAN - Pratomo, Hurip; Winarto, Adi; Rusdiyanto, Edi (LPPM Universitas Terbuka, 2010)
A research to observe sexual behavior or libido because of the treatment of pasak bumi (Eurycoma longifolia Jack) boiled water was conducted. Observation used a designed cage within an estrus female white rat partitioned by wire net. There were four variations doses of pasak bumi boiled water administered to white male mature rats. The first dose was 18 mg/200 g bw (bw= body weight), the second dose was 100 mg/200 g bw, the third dose was 200 mg/200 bw, and the control that administered aquadest 1 ml. Male rat sexual behavior characteristics were: 1. Coming near female partition, 2. Scratching/nipping partition, 3. Meet face to face. The result of the analysis showed that libido stimulated by administered pasak bumi boiled water. The best effect of libido raised by administered the first dose = 18 mg/200 g bw. Meanwhile the effect of libido of dose 2 and 3 better than the control group aquadest but lower than the effect of dose 1 did.